The traditional Greek cheese Tsalafouti: history, technology, nutrition and gastronomy - Eleni Malissiova; Ermioni Meleti; Antonia Samara; Maria Alexandraki; Athanasios Manouras (Journal of Ethnic Foods, 2023)
Abstract Tsalafouti is an ‘’unknown’’ Greek traditional cheese with great potential for getting Protected Designation of Origin accreditation and leading entrepreneurship in the area of origin. This study aimed to collect and comprehensively analyse valuable data on the history, technology, nutrition and gastronomy of Tsalafouti. A study survey was designed and 8 out of 13 Tsalafouti producers in Greece participated, providing data on Tsalafouti’s technology, quality, nutrition and history. It was revealed that there currently are some variations in Tsalafouti’s production, while the end product is of special nutritional (low in fat) and gastronomic attributes. In any case, it is apparent that food heritage and specifically dairy products heritage can possibly act as a tool for entrepreneurship, given that the special attributes that Tsalafouti may hold will be highlighted and further evidenced. Graphical Abstract